Desarrollo de un sistema para la conservación del páramo en la comunidad de Quinticusig, cantón Sigchos. - Torres Uribe, Nancy del Rocío (2023)
Anthropic and natural activities are currently environmental problems that affect the paramo of the Quinticusig community, transforming and reducing the native flora, especially the mortiño plant, the fauna and the water resource, which affects its physical characteristics, as well as economic income. of the population who live off the use of this species. The objective of this research is to develop a system for the conservation of the paramo of the Quinticusig community, Sigchos canton through the diagnosis, through the application of surveys and direct observation, the results of which allowed the development of the proposal for a conservation system of the paramo for the community to implement in the future, using participatory and responsible management strategies. The present study has a qualitative approach in which the bibliographic, inductive and direct observation methods were applied; Next, the methodology for Community Management of the Páramo was applied, as a tool that is easy to apply for the inhabitants of the community. From the results obtained, 94% of the population considers it very important to take care of the moor, preventing animals from entering and advancing the agricultural frontier because it is a supplier of water and fruit of the mortiño Vaccinium floribundum, to make wines, improving the community's economy. . In the final part, the research concludes that applying the system for the conservation of the moor contributes to the economic, environmental and tourist development of the population, improving their quality of life; In this way the proposed objectives are met.